2009
DOI: 10.1002/ijc.24444
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of human papillomavirus infection in the female population of Guatemala

Abstract: The potential introduction of the newly licensed HPV-vaccines at affordable prices could play a central role in preventing cervical cancer in middle and low-income countries, where most of the cases occur. In spite of this, basic epidemiological data about HPV and HPV-related lesions are still scarce. To determine the prevalence of cervical abnormalities, HPV prevalence, genotype distribution and related risk factors, we carried out a cross-sectional study in a population from Guatemala that included 297 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 27 publications
2
40
1
2
Order By: Relevance
“…In a study to examine barriers to HIV testing, Hong and colleagues found that perceived stigma and denial of risk were the major reasons for not seeking testing [36]. The literature documents very high rates of HPV infection in FSW, including recent data from China showing an HPV prevalence of 39% in FSW [11,16-19,29,32,37], which stands in sharp contrast to the very low level of awareness, knowledge, and perceived risk of cervical cancer in FSW in China. As demonstrated in the current study, only 15% of FSW in China ever had a Pap smear compared to 70% of their counterparts in Thailand [26].…”
Section: Discussionmentioning
confidence: 99%
“…In a study to examine barriers to HIV testing, Hong and colleagues found that perceived stigma and denial of risk were the major reasons for not seeking testing [36]. The literature documents very high rates of HPV infection in FSW, including recent data from China showing an HPV prevalence of 39% in FSW [11,16-19,29,32,37], which stands in sharp contrast to the very low level of awareness, knowledge, and perceived risk of cervical cancer in FSW in China. As demonstrated in the current study, only 15% of FSW in China ever had a Pap smear compared to 70% of their counterparts in Thailand [26].…”
Section: Discussionmentioning
confidence: 99%
“…Eduardo Franco and Luisa Villa, unpublished data, Ludwig-McGill Cohort, Brazil), and a second study in Mexico [19]. Only the carcinogenic HPV prevalence in Guatemala in a small sample of the general population [20] was comparable to the age-specific prevalence in Haiti. The age-specific prevalence of carcinogenic HPV in these Haitian women was more than twice that of immigrant Haitian women living in Little Haiti, Miami [21].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of carcinogenic HPV prevalence for selected cross-sectional studies conducted in Latin America: Haiti (from this study); Guanacaste [16]; Colombia [17], Argentina [18], Chile [17], Mexico [17]; Peru [18]; Guatemala [20]; and a second study from Mexico [19]. *estimated from graphs; †Drs.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we identified HPV 66 in women with abnormal cytology. Recently, studies made in France [26] and Guatemala [27] found the highest prevalence of HPV 66 in LSIL lesions. HPV-16 was primarily associated with the probable high-risk genotypes: HPV-53 and HPV-66.…”
Section: Hpv 66mentioning
confidence: 98%